2021
DOI: 10.1002/suco.202000700
|View full text |Cite
|
Sign up to set email alerts
|

Round robin test to compare flexural strength test methods for steel fiber‐reinforced sprayed concretes

Abstract: According to the current European standard EN 14487‐1 (residual) flexural strengths of steel fiber‐reinforced sprayed concrete are determined by performing a four‐point bending test on beams according to EN 14488‐3. Controversial to this test method, a three‐point bending test on notched square panels is recommended by EFNARC. According to EFNARC, one substantial advantage of this test method is the minor scattering of the test results. Against this background, a round robin test was performed at European leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…[1][2][3]. In addition, various admixtures modified both fresh and hardeening properties of concrete which include crumb rubber (CR) [4,5] nanomaterials [6][7][8][9], polymer materials [10][11][12], fiber-reinforcement [13][14][15][16][17], and pozzolonic materials [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]. In addition, various admixtures modified both fresh and hardeening properties of concrete which include crumb rubber (CR) [4,5] nanomaterials [6][7][8][9], polymer materials [10][11][12], fiber-reinforcement [13][14][15][16][17], and pozzolonic materials [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Mastali and Dalvand 9 studied the impact resistance, and mechanical behavior of fiber reinforced compacting concrete modified with NS and silica fume. The impact resistance is regarded as one of the critical concrete properties for applications in civil engineering Zhang et al 10 Numerous studies revealed that randomly dispersed steel fibers (SFs) could remarkably improve the concrete mechanical properties, toughness, impact resistance, post crack behavior, and fatigue properties 11–16 . For instance, Zhao et al 17 studied the combined effect of steel slag and hooked‐end SFs on the fresh and mechanical properties of self‐compacting concrete.…”
Section: Introductionmentioning
confidence: 99%